Asia Pacific Forest Genetic Resources Programme: Virtual Annual Workshop. 21 June 2021 - APFORGEN (2021)
The day’s programme consisted of presentations of country reports by APFORGEN National Coordinators and country representatives, group discussions on common interests and collaboration opportunities around APFORGEN’s strategic objectives, as well as an information session about international processes related to forest genetic resources, including the preparation of the Second State of the World’s Forest Genetic Resources report. The day was concluded by electing new members to APFORGEN’s Board for the next three-year period.